Region of the streptococcal plasmid pMV158 required for conjugative mobilization. - Priebe, S D (1989)
The nonconjugative streptococcal plasmid pMV158 can be mobilized by the conjugative streptococcal plasmid pIP501. We determined the sequence of the 1.1-kilobase EcoRI fragment of pMV158 to complete the DNA sequence of the plasmid. We showed that an open reading frame, mob (able to encode a polypeptide of 58,020 daltons), is required for mobilization of pMV158. An intergenic region present in the EcoRI fragment contains four lengthy palindromes that are found also in one or more of the staphylococcal plasmids pT181, pE194, and pUB110. One palindromic sequence, palD, which is common to all four plasmids, also appeared to be necessary for mobilization. Circumstantial evidence indicates that this sequence contains both an oriT site and the mob promoter. The Mob protein is homologous in its amino-terminal half to Pre proteins encoded by pT181 and pE194 that were shown by others to be essential for site-specific cointegrative plasmid recombination; their main biological function may be plasmid mobilization.